Hands-On Reinforcement Learning with Python : Master reinforcement and deep reinforcement learning using OpenAI Gym and TensorFlow /: Master reinforcement and deep reinforcement learning using OpenAI Gym and TensorFlow. (2018) - Ravichandiran, Sudharsan
No abstract available